i-Stow : enabling stowage planning service over the web - Aung, Kyaw Win (2014)
Since Singapore is one of the major hubs for maritime logistics in Asia, it is crucial to be efficient in planning for containers arrangement, loading and unloading for different sizes and kinds of vessels. It is quite a challenge for logistic operators to produce a feasible stowage plan for huge amount of containers. Although a previous team has already finished a program called “AutoStow” for automated stowage planning, high computation power and time is needed for generating results for large number of containers arrangements. The current AutoStow system also requires an IT technician to maintain the stowage planning program on site.